Thermo Acoustical Studies of Some Aliphatic Alcohols in Toluene with Aniline at 303 K - Thirumaran, S.; Ramya, K. (Asian Journal of Chemistry, 2010)
The ultrasonic velocity, density and viscosity have been measured for the ternary mixtures of aliphatic alcohols such as 1-propanol, 2-propanol, 1-butanol and 2-butanol with aniline in toluene at 303 K. The experimental data have been used to calculate the acoustical parameters namely adiabatic compressibility (β), free length (Lf), free volume (Vf), internal pressure (πi) and acoustic impedance (Z). The excess values of some the above parameters are also evaluated and discussed in the light of molecular interaction in the mixtures. It is observed that the alkanols form strong dipole-dipole interactions with aniline. It is also interesting to note that the specific interaction between them affects, on going to higher alcohol due to less proton-donating tendency of aniline. The donor-acceptor complexation reactions were also observed in the present study.